Facilitating Social Perspective Taking in Class through Discursive Game Design (Imaginations: Journal of Cross-Cultural Image Studies, 2025)
This paper proposes and assesses a replicable game (co)design technique to encourage social perspective taking in the higher education classroom. Fully embracing the potential of research creation approaches, this discursive game design methodology approaches games as mediators of knowledge, emphasising the process of (re)creating, modifying, and comparing different game iterations. The paper reports on two classroom exercises that draw inspiration from Dungeons & Dragons and the Checkered Game of Life to foster perspective taking across different “learner personas” and different world views. Finally, this paper discusses how notating game modifications affords continuous game-based dialogue across student generations.